Pengaruh Kelembaban Adherend pada Durabilitas Perbaikan Komposit - Masri Masri; Sugiman Sugiman (Institute of Research and Community Outreach, Petra Christian University, 2006)
In this paper, the effect of moisture on the durability of composite repair is investigated using fracture mechanics approach. The specimens of double cantilever beam were made from two composites adherend (fiberglass/unsaturated polyester) bonded by epoxy adhesives. The adherend were immersed in the distillate water to gain moisture and then dried in different drying conditions at room temperature (RT) for 12 hours followed by 100 oC for 15 minutes, 50 oC for 5 hours and 100 oC for 2.5 hours. The spesimen was wedged tested in both dry and wet condition in room temperature. The results show that the lower moisture about 2.8%wt according to drying temperature 100 oC give the better durability followed by drying temperature of 50 oC and room temperature. The indication is shown by stable crack growth at higher fracture energy and also by low crack speed at higher fracture energy. Whereas, for wet testing, the better result is reached by drying temperature of 50 oC (moisture contents of 4,4 %wt) and for dry temperature of 100 oC give the worst result. The contradiction suggested that drying temperature for adherend of composite repair should not higher than 100 oC. Abstract in Bahasa Indonesia : Dalam paper ini pengaruh kelembaban pada perbaikan durabilitas komposit fiberglass/polyester telah diselidiki dengan pendekatan fracture mechanics. Spesimen berupa Double Cantilever Beam yang terbuat dari dua adherend komposit fiberglass/polyester yang direkatkan dengan perekat epoxy. Adherend direndam dalam air distilat untuk memperoleh kelembaban dan kemudian dikeringkan dengan beberapa suhu pengeringan, yaitu suhu kamar selama 12 jam diikuti dengan 100 oC selama 15 menit, 50 oC selama 5 jam dan 100 oC selama 2,5 jam. Spesimen diuji baji pada kondisi kering (lingkungan udara) dan kondisi basah (lingkungan air). Hasil pengujian menunjukkan bahwa untuk pengujian kering, kelembaban yang rendah sesuai dengan suhu pengeringan 100 oC memberikan durabilitas yang lebih baik diikuti dengan suhu pengeringan 50 oC dan kemudian pada suhu kamar. Hal tersebut ditunjukkan dengan energi patah yang relatif cukup tinggi dan juga kecepatan retak yang rendah pada energi patah tinggi. Sedangkan pada pengujian basah, hasil yang lebih baik diperoleh pada suhu pengeringan 50 oC (kelembaban 4,4%) dan suhu pengeringan 100 oC memberikan hasil yang terendah. Hal ini menyarankan bahwa suhu pengeringan seharusnya tidak pada atau lebih tinggi dari 100 oC untuk kondisi lingkungan basah. Kata kunci: Perbaikan, kelembaban, pengeringan, double cantilever beam, uji baji, durabilitas.